Two-photon absorption laser induced fluorescence measurement of atomic oxygen density in an atmospheric pressure air plasma jet. (11th July 2016) - Conway, J; Gogna, G S; Gaman, C; Turner, M M; Daniels, S
Abstract: Atomic oxygen number density [O] is measured in an air atmospheric pressure plasma jet (APPJ) using two-photon absorption laser induced fluorescence (TALIF). Gas flow is fixed at 8 slpm, the RF power coupled into the plasma jet varied between 5 W and 20 W, and the resulting changes in atomic oxygen density measured. Photolysis of molecular oxygen is employed to allow in situ calibration of the TALIF system. During calibration, O2 photo-dissociation and two-photon excitation of the resulting oxygen atoms are achieved within the same laser pulse. The atomic oxygen density produced by photolysis is time varying and spatially non-uniform which needs to be corrected for to calibrate the TALIF system for measurement of atomic oxygen density in plasma. Knowledge of the laser pulse intensity I 0 ( t ), wavelength, and focal spot size allows correction factors to be determined using a rate equation model. Atomic oxygen is used for calibration and measurement, so the laser intensity can be increased outside the TALIF quadratic laser power dependence region without affecting the calibration reliability as the laser power dependence will still be the same for both. The atomic O density results obtained are not directly benchmarked against other known density measurement techniques. The results show that the plasma jet atomic oxygen content increases as the RF power coupled into the plasma increases.